Financial Management Related to Fiqh Muamalah in Bengkalis City - Muhammad Fadhli; Muhammad Irfan Syah; Muhammad Rizky Anes (Penerbit Jurnal Indonesia, 2023)
Humans cannot fulfill their needs only by their own efforts. There are times when you need things that are owned or managed by someone else. So to facilitate the exchange system required money. While institutions related to money are financial institutions. This research is a literature study on fiqh muamalah money and financial institutions, so that it can be seen what discussions have been researched and discussions that need to be researched. This study uses a qualitative approach. There are 30 articles published in 2021 to 2022 which are grouped into two main topics, namely the topic of money and the topic of financial institutions. The topic of discussion of money is then grouped into three sub-topics, namely: 1) dinar dirham, 2) the use of E-Money, and 3) virtual currency (cryptocurrency). And the topic of discussion of financial institutions is also grouped into three sub-topics, namely: 1) implementation of contracts at financial institutions, 2) management of financial institutions, and 3) supervision of financial institutions. The topic of financial institutions with sub-topics of contract implementation at financial institutions is the most articles with a 33.4% presentation. While the articles that were the least discussed were the dinar and dirham sub-topics on the topic of money, with a presentation of 3.3% of the overall theme of money and financial institutions. Discussions that need to be researched, such as: the law of buying and selling currency in Islam, the exchange rate in the perspective of Islamic economics, monetary in the view of Islam and the relationship between money and financial institutions in fiqh muamalah.